Special Form Hankel Matrix Inverses (n+1)×(n+1),n≥3 With 2×2 Block Matrices - Rahma, Ade Novia; Azzahra, Frista; Aryani, Fitri; Rahmawati, Rahmawati (Universitas Islam Madura, 2025)
This study aims to determine the inverse of a special form Hankel matrix using a block matrix. In this study, some steps are carried out. The first step will be given a special form Hankel matrix which will then be blocked into a block matrix. Next, determine the inverse of the invertible submatrix of the Hankel matrix so that the general form is obtained. The last step is seen from the inverse pattern of the two ways of blocking the Hankel matrix of the unique structure of order to so that the general shape of the inverse Hankel matrix of special form is obtained. The results obtained will be obtained in the general structure of the Hankel matrix inverse special form, using a block matrix.